Unraveling the invasiveness of Prosopis juliflora (Neltuma juliflora): seed traits and ecological implications - Chibani, Kamel; Fan, Mengjie; Ali, Hamada E.; Al-Kharusi, Laya (Frontiers in Plant Science, 2026)
Prosopis juliflora (Neltuma juliflora) is a globally invasive tree species threatening arid ecosystems. Its invasion success is driven by specific seed traits that function as an adaptive bet-hedging strategy. The impermeable seed coat enforces physical dormancy and enables the formation of a persistent soil seed bank that buffers against environmental stochasticity (population insurance). Conversely, rapid germination allows the species to exploit short-lived moisture pulses and outcompete native vegetation. Livestock-mediated endozoochory further facilitates directed dispersal by depositing scarified seeds in favorable microsites. This mini-review synthesizes current knowledge on these anatomical and physiological mechanisms and examines how they interact with climate change variables, specifically rising temperatures and altered precipitation on intensifying invasion dynamics. Finally, we discuss integrated management strategies targeting seed bank depletion and dispersal pathways.